Hydrothermal alteration of medium-grade metamorphic rocks of Metsämonttu VMS deposit, southern Finland : A comparative portable XRD and near-infrared spectroscopy analysis - Siira, Jenniina (My University, 2021)
Hydrothermal alteration processes are connected to the formation of many economically important ore deposits. This study represents a comparative portable XRD (pXRD) and near-infrared (NIR) spectroscopy analysis of four drill cores of Metsämonttu volcanogenic massive sulphide (VMS) deposit, southwestern Finland. The drill cores represent hydrothermally altered low-grade metamorphic lithologies of lower amphibolite facies. The NIR spectroscopy focuses on short-wave infrared (SWIR; 1.0-2.5 μm) analysis with some supplementing visible, near-infrared (VNIR; 0.4-1.0 μm) data. The SWIR and VNIR data were gathered with ASD Terraspec 4 Portable NIR Spectrometer as point measurements and were interpreted with The Spectral Geologist software. The pXRD data were measured using Olympus Portable Onsite XRD Terra-542 device and were interpreted with XPowder software. In this study, the mineral assemblages identified with the pXRD, and the SWIR spectroscopy are compared to the petrophysical and geochemical data measured with portable X-ray fluorescence (pXRF). The SWIR data are connected to the lithological data by using the wavelength positions of AlOH, FeOH, and MgOH absorption features and identifying the mineralogical alterations pointed by them. The pXRD measurements used in this study show to have quality issues like rising of the diffractogram background with the samples including sulphidic minerals, especially galena. Another quality issue is observed with the samples including minerals with preferred orientations, particularly muscovite. High amount of amorphous, or nanocrystalline material of extremely fine grain size in the sample is one uncertainty factor that is shown to produce quality problems to the diffractograms. Due to previously mentioned and several other quality issues such as short measurement time and low resolution, the method is shown not to be reliable enough to be used in identification of minor mineral phases (<5 wt%) or accessory minerals. Furthermore, it is shown that the point measurements done with the spectrometer, using the SWIR and VNIR wavelengths, have their limitations regarding the number of minerals that could have been identified. In addition, the representativeness of the point measurements is shown to be limited. However, both the pXRD and the SWIR spectroscopy describe the mineral variation in a different manner. The pXRD data are used to identify most of the major mineral phases in the sample, while the SWIR data are used to observe chemical alterations of white mica and chlorite group phases. The study identifies the alterations of the altered rocks of the Metsämonttu deposit by combining the pXRD and the SWIR data with the pXRF and the petrophysical data, and specifies the information related to the previously logged lithological units. This approach is a suggested way to overcome the limitations of each method.

Hydrotermiset muuttumisprosessit ovat yhteydessä monien taloudellisesti merkittävien malmivarantojen syntyyn. Tässä työssä esitetään vertaileva kannettavalla röntgendiffraktioanalysaattorilla (pXRD) ja lähi-infrapunaspektroskopialla (NIR) tehty analyysi neljästä kairasydämestä, jotka on kairattu Metsämontun vulkanogeenisesta massivisesta sulfidiesiintymästä (VMS). Kairasydämet edustavat matalan metamorfoosiasteen alemman amfiboliittifasieksen litologioita. NIR-spektroskopia keskittyi lyhytaaltoisen infrapuna-alueen (short-wave infrared, SWIR; 1.0-2.5 μm) mittauksiin, joita täydennettiin näkyvän valon lyhytaaltoisen infrapuna-alueen (visible, near-infrared, VNIR; 0.4-1.0 μm) mittausaineistolla. SWIR- ja VNIR-aineisto kerättiin ASD Terraspec 4 Portable NIR -spektrometrillä pistemittauksina ja tulkittiin The Spectral Geologist -ohjelmistolla. pXRD-aineisto kerättiin käyttäen Olympus Portable Onsite XRD Terra-542 -laitteistoa ja tulkittiin XPowder-ohjelmistolla. pXRD:llä ja SWIR-spektroskopialla havaittuja mineraalikokoonpanoja vertailtiin petrofysikaaliseen ja kannettavalla röntgenfluoresenssilaitteistolla (pXRF) mitattuun geokemialliseen aineistoon. SWIR-aineisto yhdistettiin litologiseen aineistoon käyttämällä Al-, Fe- ja Mg-hydroksidien absorptiokäyrien sijaintien vaihtelua ja havainnoimalla mineralogista muuttumista niiden kautta. pXRD-mittauksien laatuongelmia, kuten diffraktogrammien taustojen nousua, ilmeni sulfideja, etenkin lyijyhohdetta, sisältävissä näytteissä. Toinen laatuseikka liittyi näytteisiin, jotka sisälsivät preferoitua orientaatiota suosivia mineraaleja, kuten muskoviittia. Paljon amorfista tai nanokiteistä, erittäin hienojakoista materiaalia sisältävät näytteet ovat epävarmuustekijöitä, jotka aiheuttivat laatuongelmia diffraktogrammeihin. Edellämainituista sekä useista muista virhelähteistä, kuten lyhyestä mittausajasta ja alhaisesta resoluutiosta johtuen metodia ei voida todeta luotettavaksi pieninä pitoisuuksina (<5 wt%) esiintyvien mineraalien ja aksessoristen mineraalien tunnistamisessa. SWIR- ja VNIR-spektroskopialla tehdyillä pistemittauksilla havaittiin olevan omat rajoitteensa siinä, kuinka paljon eri mineraalifaaseja niillä voidaan tunnistaa. Pistemittausten edustavuus on myös rajallinen. pXRD ja SWIR-spektroskopia kuvaavat mineraalien vaihtelua eri tavoin. pXRD-aineistoa käytetään yleisimpien päämineraalien tunnistuksessa, kun taas SWIR-aineistoa käytetään vaaleiden kiilteiden ja kloriitti-ryhmän mineraalien kemiallisen vaihtelun havaitsemiseen. Yhdistämällä pXRD- ja SWIR-aineistoista saatua tietoa petrofysikaaliseen ja pXRF-aineistoon on voitu tunnistaa eri muuntumistyyppejä Metsämontun esiintymän muuntuneissa kivissä, ja jo olemassa olevia tietoja litologisista yksiköistä on voitu tarkentaa.. Tämä lähestymistapa on suositeltava ja sillä voidaan kompensoida eri menetelmien puutteita.
Keywords: Metsämonttu, near-infrared (NIR) spectroscopy, portable X-ray diffraction (pXRD), volcanogenic massive sulphide (VMS) deposits, hydrothermal alteration